Performance Evaluation of IDMP’s QoS Framework - WU, Wei (Institutional Knowledge at Singapore Management University, 2002)
The intra-domain mobility management protocol (IDMP) has been proposed as a protocol for managing IP mobility within a cellular access network. This paper evaluates the performance of IDMP's quality of service (QoS) framework, which uses a modified form of the differentiated services architecture, with a centralized bandwidth broker performing admission control and resource provisioning for different traffic classes. While experimental results demonstrate that our IDMP-based QoS mechanism is able to support differential performance guarantees for mobile users with fairly low latency overheads, analytical derivations show that this QoS support can be achieved with only a marginal increase in the signaling cost.